Meta-analysis of the Correlation Between Interleukin-6 Promoter Polymorphism -174G/C and Interferon Regulatory Factor 4 rs12203592 Polymorphism With Skin Cancer Susceptibility. (November 2016) - Wu, Miao; Cao, Yi; Liu, Yong-lin; Ma, Li-li; Yang, Xiao-hong
Abstract : Inflammation is a process whereby the immune system responds to a disease or injury. Chronic inflammation, however, has been linked to several types of cancers such as skin cancer. Molecular epidemiological studies were carried out in recent years evaluating interferon regulatory factor 4 (IRF4) rs12203592 and interleukin-6 (IL-6) gene -174G/C polymorphism associated with skin cancer risk for different groups of people. However, the results are still conflicting, not conclusive. We performed a meta-analysis to investigate the association between cancer susceptibility and IL-6 -174G/C (1130 cases and 1260 controls from 7 studies) and IRF4 rs12203592 polymorphisms (3879 cases and 6759 controls from 9 studies) in different inheritance models. We assess the strength of association of odds ratio (ORs), 95% confidence interval (CI). Overall, significantly elevated skin cancer risk was found when all studies were pooled into the meta-analysis of IL-6 -174G/C (For GC vs. GG: OR = 1.28, 95% CI, 1.06–1.54, I 2 = 0, P heterogeneity = 0.816; for CC/GC vs. GG: OR = 1.26, 95% CI, 1.05–1.50, I 2 = 0, P heterogeneity = 0.618). However, for IRF4 rs12203592 polymorphism, significantly increased risk of skin cancer was observed in TT versus CC (OR = 1.99, 95% CI, 1.30–3.07, I 2 = 76.7%, P heterogeneity < 0.001) and in recessive model (OR = 1.91, 95% CI, 1.31–2.77, I 2 = 69.9%, P heterogeneity < 0.001). This meta-analysis indicates that the IL-6 gene -174G/C and IRF4 rs12203592 polymorphisms may be associated with an increased skin cancer risk.